A Review of the Literature on LGBTQ Adults Who Experience Homelessness. Issue 3 (23rd February 2019) - Ecker, John; Aubry, Tim; Sylvestre, John
ABSTRACT: Little is known about lesbian, gay, bisexual, transgender, and queer (LGBTQ) adults who experience homelessness. The current review critically analyzes the scant literature on LGBTQ adults who experience homelessness, with a particular focus on: (1) pathways into homelessness; (2) support needs; (3) targeted programming; and (4) exits out of homelessness. A total of 143 articles were identified, and 16 articles met the criteria of appropriate age range, article quality, and relevance of topic. Results from this review demonstrate that homeless LGBTQ adults have unique physical and mental health challenges, largely concerning HIV and substance use. Transgender and gender non-conforming adults who experience homelessness encounter several challenges in the homelessness system, particularly in regard to safety and gender-affirming supports. Recommendations focus on practical implications for support and suggestions for future research.